Avaliação da toxicidade aguda do uso não médico do modafinil - Prado, Luciane Dellazari da Silva do (2025)
Modafinil (2-benzhydryl sulfinyl acetamide) is a wakefulness-promoting psychostimulant drug used to treat sleep disorders such as narcolepsy, daytime sleepiness, and sleep apnea. Its consumption is currently increasing, aiming to improve alertness and cognitive performance even in healthy individuals. However, this abusive and indiscriminate use is a concern, especially in young adults and adults. Therefore, the main objective of this study was to elucidate the toxicity of off-label modafinil using the zebrafish (Danio rerio) as an animal model. For this purpose, zebrafish were acutely exposed to different concentrations: a control group of 0 mg. L-1 and those exposed to modafinil at concentrations of 200 mg. L-1, 400 mg. L-1, and 600 mg. L-1 for 15 min. At the end of the exposures, we assessed the impact on cognition and memory, sociability, fear, anxiety, locomotion, and endurance through behavioral tests such as the new-tank test, social preference, light-dark test, Y-maze test, and forced swim test. After euthanasia, assessments were performed on cortisol levels, non-protein thiols, lipid peroxidation, and mitochondrial complex activity. The data indicated that modafinil at the highest concentration induced a pattern of hyperactivity, characterized by a greater distance traveled and variability in turning angles in the new-tank test. However, at an intermediate concentration of the 400 mg. L-1 fish showed a mild anxiogenic effect, evidenced by an increased latency to enter the upper zone, suggesting hesitation in exploring the upper part of the tank. Similarly, in the light-dark test, fish exposed to the highest concentration showed a greater latency to enter the light zone, indicating cautious and possibly anxiogenic behavior. Furthermore, our results showed that in the forced swimming test, fish exposed to a concentration of 400 mg/L-1 of modafinil presented greater latency to enter the central zone, that xiii is, they remained swimming for longer in the external zone before being dragged to the center, which suggests greater locomotor resistance or sustained motor effort at this concentration. However, no social or memory alterations were observed in fish exposed to the different concentrations. The results also indicate increased total protein levels at the highest concentration, possibly associated with adaptive inflammatory responses. However, further investigation is needed to fully explore the mechanisms involved. Exposure to 200 mg L-1 led to increased lipid peroxidation; this increase at the lowest concentration may indicate that modafinil induced damage without promoting an efficient adaptive response. No changes were observed in the analyses of cortisol levels, non-protein thiols, and mitochondrial complex activity. Therefore, our study demonstrates that acute exposure to modafinil can induce neurobehavioral changes and changes in oxidative stress, since it showed an increase in the lowest concentration. However, in this work, it does not appear to be the most relevant pathway of toxicity, therefore, there is a need for greater attention to the potential risks in the off-label use of this drug.